"Romantic Entertainers" on Kenya's Coastal Tourism: A Case of Sex Tourism. (1st July 2020) - Omondi, Rose; Ryan, Chris
Abstract: This paper results from a year-long ethnographic study spent with a group of women on the Kenyan coastline who provide older male European tourists with friendship and intimacy. However, for the most part these are asymmetric relationships for while in many instances the men experience emotional feelings of tenderness for their girl-friends (albeit based on concepts of being with an "exotic" woman), for the women a mzungu (a foreign long-term male client perceived as wealthy) represents a potential richer life-style. The paper describes the practices engaged in by the women as they entertain their clients in a theater of romance based often on a deceit and where to survive emotions are on the one hand faked and on the other require self-delusion and distancing.